1994
DOI: 10.1177/019874299401900401
|View full text |Cite
|
Sign up to set email alerts
|

Description and Evaluation of the Job Designs Project for Adolescents and Young Adults with Emotional or Behavioral Disorders

Abstract: This article describes the Job Designs Project, a 3-year model demonstration effort that provided vocational services to adolescents and young adults with emotional or behavioral disorders. Vocational trainers offered job placement, training, and support to the participants. Of the 58 participants, 46 (79%) secured competitive work and 17 of the 46 were placed in multiple job placements, resulting in a total of 78 competitive jobs. Of the 78 jobs, 51 (65%) ended successfully (e.g., the worker quit the job appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…In the Job Designs project, Bullis et al (1994), reported that one year after working with youth with ED on transition issues, those employed were working an average of 16.6 hours per week at an average hourly wage of $4.51. Youth and young adults in RENEW, in contrast, were averaging 28.3 hours per week and $6.49 per hour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Job Designs project, Bullis et al (1994), reported that one year after working with youth with ED on transition issues, those employed were working an average of 16.6 hours per week at an average hourly wage of $4.51. Youth and young adults in RENEW, in contrast, were averaging 28.3 hours per week and $6.49 per hour.…”
Section: Resultsmentioning
confidence: 99%
“…necessary (Cook, Razzano, Straiton, & Ross, 1994). Finally, adjusting to workplace demands and displaying appropriate social-interpersonal skills on the job are important areas for persons with ED or MI and strongly related to employment success (Bullis, Fredericks, Lehman, Paris, Corbitt, & Johnson, 1994) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in Oregon, Doren ( 1992) found that participants with ED admitted to using alcohol in excess of these heavy user percentages and used other illicit drugs on par with these rates. Also, in one of the vocational and transition projects we have conducted (Bullis, Fredericks, Lehman, Paris, Corbitt, & Johnson, 1994 ), we found that more than 70% of the participants had been treated for substance abuse upon entry into the program. Further, a history of substance abuse and substance use while receiving services were strongly related to success in job placement .…”
Section: Social Experiencesmentioning
confidence: 97%
“…Surveys and focus groups we have conducted of the employers who hire workers from our programs suggest that most employers hire participants for three main reasons: (a) they want to offer assistance to someone in need, providing a service to the community, (b) they are impressed with the staff person who made the job development contact, or ( c) they have had positive experience with other such programs in the past (Bullis, Fredericks, Lehman, Paris, Corbitt, & Johnson, 1994;Cheney et al, 1998a).…”
Section: Competitive Employmentmentioning
confidence: 99%